2013
DOI: 10.3389/fnhum.2013.00269
|View full text |Cite
|
Sign up to set email alerts
|

tDCS stimulation segregates words in the brain: evidence from aphasia

Abstract: A number of studies have already shown that modulating cortical activity by means of transcranial direct current stimulation (tDCS) improves noun or verb naming in aphasic patients. However, it is not yet clear whether these effects are equally obtained through stimulation over the frontal or the temporal regions. In the present study, the same group of aphasic subjects participated in two randomized double-blind experiments involving two intensive language treatments for their noun and verb retrieval difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
76
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(81 citation statements)
references
References 47 publications
(98 reference statements)
2
76
0
3
Order By: Relevance
“…Several studies have already applied tDCS to Broca’s area in patients following stroke and found beneficial effects in language recovery (Fiori et al, 2013; Marangolo & Caltagirone, 2014; Marangolo et al, 2014; Monti et al, 2008), however one study found no benefit (Polanowska, Lesniak, Seniow, & Czlonkowska, 2013). These studies, taken with the current findings, support the use of anodal tDCS to both the left PFC and PPC to enhance LTM skills.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already applied tDCS to Broca’s area in patients following stroke and found beneficial effects in language recovery (Fiori et al, 2013; Marangolo & Caltagirone, 2014; Marangolo et al, 2014; Monti et al, 2008), however one study found no benefit (Polanowska, Lesniak, Seniow, & Czlonkowska, 2013). These studies, taken with the current findings, support the use of anodal tDCS to both the left PFC and PPC to enhance LTM skills.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, cathodal tDCS decreases cortical excitability, shifting the resting membrane potential toward hyperpolarization and reducing the firing rate of neurons [7][8][9]. A small but growing body of evidence has already indicated that tDCS may provide a supplementary treatment approach for different language deficits in patients with chronic stroke-induced aphasia, such as word-finding difficulties [10][11][12][13], non-fluent speech [12,14] and articulatory disorders [15][16][17][18][19]. In fact, in a preliminary study on a small sample of chronic patients, Marangolo et al [15] showed that repetitive anodal tDCS over the left inferior frontal gyrus (IFG), coupled with language training helped patients to recover from their articulatory disturbances.…”
mentioning
confidence: 86%
“…Tasks employed in these studies include fluency, interference, picture naming, verbal learning, and proper noun learning. In clinical populations, tDCS has been used mainly to improve motor and language recovery, primarily after stroke 5961, 8693 A wide range of tasks have been targeted in post-stroke aphasia including: verb naming 89 , auditory verbal working memory 93 , repetition of syllables and words for treatment of speech apraxia 94 , word retrieval or picture naming for anomia treatment 61, 70, 75, 88, 92, 95 . Despite the plethora of reports on language recovery using tDCS after stroke, only a few studies have examined it in neurodegenerative diseases (see recent reviews 96, 97 ): three studies on AD 62, 77, 98 , including only one study in which tDCS was applied for more than one session (five sessions) 80 and which showed greater improvement with tDCS vs. sham in a visual recognition task (9% vs. 2.6%) but without any task performed during either tDCS or sham conditions, two studies on frontotemporal dementia (FTD) 99, 100 (one session only with no effect of tDCS 99 but also no task practiced during treatment, and 10 sessions with more improvement over tDCS vs. sham 100 coupled with an oral naming task), and ours in PPA 101 where (after 15 treatment sessions coupled with a spelling task) we found greater improvement with tDCS vs. sham (35% of patients made significant improvement on untrained words with tDCS vs. 16% of patients made significant improvement on untrained words with sham).…”
Section: Introductionmentioning
confidence: 99%